Bounding the Causal Effect of Unemployment on Mental Health: Nonparametric Evidence from Four Countries - Kamila Cygan-Rehm; Daniel Kühnle; Michael Oberfichtner (Institute of Labor Economics (IZA), 2017)
An important, yet unsettled, question in public health policy is the extent to which unemployment causally impacts mental health. The recent literature yields varying findings, which are likely due to differences in data, methods, samples, and institutional settings. Taking a more general approach, we provide comparable evidence for four countries with different institutional settings Australia, Germany, the UK, and the US using a nonparametric bounds analysis. Relying on fairly weak and partially testable assumptions, our paper shows that unemployment has a significant negative effect on mental health in all countries. Our results rule out effects larger than a quarter of a standard deviation for Germany and half a standard deviation for the Anglo-Saxon countries. The effect is significant for both men and women and materialises already for short periods of unemployment. Public policy should hence focus on early prevention of mental health problems among the unemployed.
Keywords: I12; J64; 330; mental health; unemployment; bounds